COPING BEHAVIOR OF BENJAMIN BUTTON IN ERIC ROTH’S THE CURIOUS CASE OF BENJAMIN BUTTON MOVIE (2008): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - PURWANTORO, IMAN HARSE (2010)
The major problem of this study is to reveal the coping behavior of Benjamin Button reflected in The Curious Case of Benjamin Button movie. The objectives of the study are; to analyze the structural elements of the movie and to analyze the character of Benjamin Button based on individual psychological analysis.